Managers Handling Disputes: Third-Party Roles and Perceptions of Fairness - Karambayya, Rekha; Brett, Jeanne M. (Academy of Management Journal, 1989)
This study investigated how managers resolve disputes in organizations, comparing a typology of managerial third-party dispute-resolution behavior drawn from prior research to the behavior of management students playing third parties in dispute-resolution simulations. We evaluated the third parties' behavior against standard measures of procedural and distributive justice, making this the first study of managerial dispute-resolution behavior that investigates the relationships among third-party behavior, the type of resolution achieved, and perceptions of justice.